2010
DOI: 10.1100/tsw.2010.214
|View full text |Cite
|
Sign up to set email alerts
|

Two Faces of Protein Kinase Cδ: The Contrasting Roles of PKCδ in Cell Survival and Cell Death

Abstract: Protein kinase Cδ (PKCδ) is a member of the PKC family that plays a critical role in the regulation of various cellular processes, including cell proliferation, cell death, and tumor promotion. Since the identification that PKCδ is a substrate for caspase-3, there has been overwhelming literature that linked PKCδ with proapoptotic signaling. While PKCδ generally functions as a proapoptotic protein during DNA damage-induced apoptosis, it can act as an antiapoptotic protein during receptor-initiated cell death. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(129 citation statements)
references
References 100 publications
3
126
0
Order By: Relevance
“…4,12 Numerous studies have shown that PKCd is involved in proapoptic signaling upon phorbol ester stimulation and after DNA damage. 13 Therefore, we tested PMAinduced cell death in the patient's cells (EBV-transformed B cells and PBMCs). Although treatment with PMA induced 60% and 50% cell death in EBV-transformed B cells (Figure 6A-B) and PBMCs from normal control patients ( Figure 6C), respectively, the patient's cells were completely resistant to BLOOD, 18 APRIL 2013 x VOLUME 121, NUMBER 16 PKCd DEFICIENCY CAUSES ALPS-LIKE DISEASE 3121…”
Section: Pma-induced Apoptosis Is Defective In Pkcd Deficiencymentioning
confidence: 99%
“…4,12 Numerous studies have shown that PKCd is involved in proapoptic signaling upon phorbol ester stimulation and after DNA damage. 13 Therefore, we tested PMAinduced cell death in the patient's cells (EBV-transformed B cells and PBMCs). Although treatment with PMA induced 60% and 50% cell death in EBV-transformed B cells (Figure 6A-B) and PBMCs from normal control patients ( Figure 6C), respectively, the patient's cells were completely resistant to BLOOD, 18 APRIL 2013 x VOLUME 121, NUMBER 16 PKCd DEFICIENCY CAUSES ALPS-LIKE DISEASE 3121…”
Section: Pma-induced Apoptosis Is Defective In Pkcd Deficiencymentioning
confidence: 99%
“…It is generally believed that the activation of PKC isoforms contributes to cancer, but downregulation rather than activation of PKCd has been associated with tumor progression (7). While some studies point to a role of PKCd in cell survival and the antiapoptotic response, most studies indicate that the PKCd isoform promotes suppression of cell proliferation and apoptosis induction.…”
Section: Introductionmentioning
confidence: 99%
“…42 We found that both Bcl-xL and Bax expressions are significantly modulated in differentiating MKs, with a kinetic similar to PKCε and PKCδ, respectively ( Figure 1A,C).…”
Section: Pkcδ/pkcε and Bax/bcl-xl Expression Levels Are Differently Mmentioning
confidence: 77%